Penetrating pharynx wound reaching mediastinum. Which is the proper surgical approach? - Rivero Fernández I; Montojo Woodeson J; Sanz Rodríguez M; García Fernández A; Gavilanes-Plasencia J (Global Journal of Medical and Clinical Case Reports - Peertechz Publications, 2021)
We report the case of a knife penetrating wound from the hypopharynx-cervical esophagus area to the posterior mediastinum in a 91-year-old patient. The surgical approach for this patient required a transoral examination with direct laryngoscopy and a right cervicotomy. Although it was not necessary to perform a thoracotomy, the position of the knife, stuck towards the posterior mediastinum, made the presence of an interdisciplinary team in the operating room necessary.